The Functions of Social Capital and Local Wisdom in Handling Covid-19 Pandemic in West Kalimantan - Ersa Tri Fitriasari (International Journal of Science and Society, 2022)
Covid-19 has caused anxiety in the world community. This impacts the multicultural community in West Kalimantan in response to the Covid-19 pandemic. Some efforts are made with social capital and local wisdom in the form of the Tolak Bala ritual as prevention so that the pandemic does not have a broad impact. This study aims to reveal the function of community social capital towards the values of local wisdom in the form of traditional rituals practiced by multicultural communities in pleading to prevent the spread of Covid-19. The subjects in this study were traditional leaders and people from various ethnic groups in West Kalimantan. The results show that the function of social capital and local wisdom used with different rituals and traditional ceremonies is a form of self-defense to avoid Covid-19.